Virtual Assets, Real Tax: The Capital Gains/Ordinary Income Distinction In Virtual Worlds - Beekman, Nell A. (Science and Technology Law Review, 2009)
A great deal of economic activity now occurs in virtual worlds, raising questions about the proper taxation of income generated by virtual world activity. This Note focuses on the characterization of such income, that is, whether income earned in virtual worlds should be classified as ordinary income or capital gains. Generally, the character of income is determined by the activity which generated the income. In the context of virtual worlds, the issue is whether character should be determined by the nature of the user’s transactions within the world. As argued below, there is no good conceptual justification for treating economic activity in virtual worlds differently from analogous activity that occurs in the real world. However, applying the capital gains-ordinary income distinction to virtual worlds would not be administratively feasible. Thus, for the reasons set forth in this Note, the best possible tax regime is to classify all income earned in virtual worlds as ordinary income.